Anatomical study of the zygomatic and buccal branches of the facial nerve: Application to facial reanimation procedures. Issue 4 (31st January 2019) - Kehrer, Andreas; Engelmann, Simon; Ruewe, Marc; Geis, Sebastian; Taeger, Christian; Kehrer, Michael; Prantl, Lukas; Tamm, Ernst; Bleys, Ronald R.L.A.W.; Mandlik, Veronika
Abstract : The facial nerve is responsible for any facial expression channeling human emotions. Facial paralysis causes asymmetry, lagophthalmus, oral incontinence, and social limitations. Facial dynamics may be re‐established with cross‐face‐nerve‐grafts (CFNG). Our aim was to reappraise the zygomaticobuccal branch system relevant for facial reanimation surgery with respect to anastomoses and crossings. Dissection was performed on 106 facial halves of 53 fresh frozen cadavers. Study endpoints were quantity and relative thickness of branches, correlation to "Zuker's point", interconnection patterns and crossings. Level I and level II branches were classified as relevant for CFNG. Anastomoses and fusion patterns were assessed in both levels. The zygomatic branch showed 2.98 ± 0.86 (range 2–5) twigs at level II and the buccal branch 3.45 ± 0.96 (range 2–5), respectively. In the zygomatic system a single dominant branch was present in 50%, two co‐dominant branches in 9% and three in 1%. In 66% of cases a single dominant buccal twig, two co‐dominant in 12.6%, and three in 1% of cases were detected. The most inferior zygomatic branch was the most dominant branch ( P  = 0.003). Using Zuker's point, a facial nerve branch was found within 5 mm in all facial halves. Fusions were detected in 80% of specimens. Two different types of fusion patterns could be identified. Undercrossing of branches was found in 24% at levels I and II. Our study describes facial nerve branch systems relevant for facial reanimation surgery in a three‐dimensional relationship of branches to each other. Clin. Anat. 32:480–488, 2019. © 2019 Wiley Periodicals, Inc.